Investigation of Two Distinct Flavone Synthases for Plant-Specific Flavone Biosynthesis in Saccharomyces cerevisiae - Leonard, Effendi (American Society for Microbiology, 2005)
Flavones are plant secondary metabolites that have wide pharmaceutical and nutraceutical applications. We previously constructed a recombinant flavanone pathway by expressing in Saccharomyces cerevisiae a four-step recombinant pathway that consists of cinnamate-4 hydroxylase, 4-coumaroyl:coenzyme A ligase, chalcone synthase, and chalcone isomerase. In the present work, the biosynthesis of flavones by two distinct flavone synthases was evaluated by introducing a soluble flavone synthase I (FSI) and a membrane-bound flavone synthase II (FSII) into the flavanone-producing recombinant yeast strain. The resulting recombinant strains were able to convert various phenylpropanoid acid precursors into the flavone molecules chrysin, apigenin, and luteolin, and the intermediate flavanones pinocembrin, naringenin, and eriodictyol accumulated in the medium. Improvement of flavone biosynthesis was achieved by overexpressing the yeast P450 reductase CPR1 in the FSII-expressing recombinant strain and by using acetate rather than glucose or raffinose as the carbon source. Overall, the FSI-expressing recombinant strain produced 50% more apigenin and six times less naringenin than the FSII-expressing recombinant strain when p-coumaric acid was used as a precursor phenylpropanoid acid. Further experiments indicated that unlike luteolin, the 5,7,4′-trihydroxyflavone apigenin inhibits flavanone biosynthesis in vivo in a nonlinear, dose-dependent manner.